2021
DOI: 10.6007/ijarbss/v11-i5/9924
|View full text |Cite
|
Sign up to set email alerts
|

Toward the Community-based Sustainable Marine Tourism: Identifying the Impact of Tourism Development in Karimunjawa Island

Abstract: This paper aims to assess the impact of conventional tourism development in Karimunjawa Island in Indonesia. This paper considers the impact from the perspective of local people in three sustainable tourism development aspects: economic, environmental, and sociocultural. In addition, this paper explores the perspective of the local people to support the initiation of community-based sustainable marine tourism in Karimunjawa Island, Indonesia. This paper employed mixed methods, and the data were collected throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
1
2
0
1
Order By: Relevance
“…Waste management as a challenge aligns with (Rai, 2019) [54] who reported that with the increase in the number of visitors, there is increase in the production of the waste generation. It is also consistent with (Wijaya et al, 2021), where the authors reported that in addition to the economic and social implications observed in Karimunjawa Island of Indonesia, tourism-related environmental effects may in the future affect the quality of life in the community. Many respondents of their study admitted that there was a significant amount of plastic waste from food and beverage packaging.…”
Section: Tourism Levy Bill Of Bhutan 2022supporting
confidence: 87%
See 1 more Smart Citation
“…Waste management as a challenge aligns with (Rai, 2019) [54] who reported that with the increase in the number of visitors, there is increase in the production of the waste generation. It is also consistent with (Wijaya et al, 2021), where the authors reported that in addition to the economic and social implications observed in Karimunjawa Island of Indonesia, tourism-related environmental effects may in the future affect the quality of life in the community. Many respondents of their study admitted that there was a significant amount of plastic waste from food and beverage packaging.…”
Section: Tourism Levy Bill Of Bhutan 2022supporting
confidence: 87%
“…On the other hand, a study conducted by Nguyen andSerrao-Neuman (2022) [57] in KhanhHoa Province of Vietnam, reported that due to a sharp increase in the number of visitors, KhanhHoa province's tourism industry has improved the quality of social life for the region's indigenous population resulting in an upgraded system of restaurants and hotels that cater to tourists' needs. Further Wijaya et al (2021) [80] authors also mentioned that CBST not only helps in improving the quality of life of indigenous population but also it helps in gaining skills and knowledge through various training facilitated by both CBST and the local government. For example, homestay management training, English language training for tour guides, and training on making food.…”
Section: Research Question 1: Perception Of Community On the Communit...mentioning
confidence: 99%
“…Kementerian Pariwisata dan Ekonomi Kreatif (Kemenparekraf) mencatat, pada tahun 2023 terdapat sekitar 4,674 desa wisata yang tersebar di seluruh wilayah Indonesia. Beberapa diantaranya sudah memenuhi kriteria desa wisata mandiri budaya, kreatif dalam hal pemanfaatan digitalisasi promosi desa wisata, memiliki kelembagaan desa wisata dan sertifikasi cleanliness, health, safety, and environment sustainability (CHSE) berstandar nasional (Wijaya et al, 2021). Dinas Pariwisata Daerah Istimewa Yogyakarta (DIY) mencatat setidaknya terdapat 205 desa wisata di tahun 2023, 100 diantaranya merupakan desa wisata rintisan, 54 merupakan desa berkembang, 37 merupakan desa maju dan 14 desa merupakan desa mandiri (Bapeda Provinsi Yogyakarta, 2023).…”
Section: Pendahuluanunclassified
“…Therefore, this paper aims to describe the ecological problems raise in Karimunjawa Island as the impact of marine tourism activities. As we understand, a glimpse of environmental problems in Karimunjawa cannot be avoided [7]. Many studies have been conducted on Karimunjawa Island in various aspects: geographical, social, economic, ecological, and tourism.…”
Section: Introductionmentioning
confidence: 99%